N. Petrus Pons (Ed.) (2016). Alchoranus Latinus quem transtulit Marcus canonicus Toletanus. Madrid: Consejo Superior de Investigaciones Científicas. CLXX +464 pp. - Rivera Luque, José Luis Alexis (Estudios de Asia y África, 2018)
N. Petrus Pons (Ed.) (2016). Alchoranus Latinus quem transtulit Marcus canonicus Toletanus. Madrid: Consejo Superior de Investigaciones Científicas. CLXX +464 pp.